The Role and Potential of Blockchain Technology for the Food Processing Industry: A Scoping Review - Adrian Oțoiu; Daniela Ioana Manea; Dorel Mihai Paraschiv; Alexandra Ștefan (Amfiteatru Economic)
Through its multiple applications such as traceability and optimization of the food supply chain, achieving food safety and reducing food waste or implementing smart contracts, blockchain technology is proving its usefulness in the food processing and distribution industry. Stimulated by the current advances and the high interest in this relatively recently emerged topic, characterized by a limited number of implementations in the food industry, the paper aims to conduct a bibliometric scoping review. This type of analysis provides an overview of the aspects, applications and technical details of the implementation of this technology in the food sector. A survey of the relevant literature, still in its infancy, reveals recent solutions and implementations that have the potential to exert a major influence on developments in the field. In contrast to existing review-type analyses, this paper incorporates the key aspects of blockchain technology implementation related to food processing, distribution, traceability and pricing. The paper summarizes the benefits but also the challenges related to the adoption of blockchain technology in agri-food, providing a comprehensive perspective on the state of the art and its essential role in ensuring sustainable agricultural production, reducing food waste, improving food security and integrating into a circular and resilient economic framework. Therefore, blockchain-based technologies reveal themselves as important tools for implementing the EU’s “Farm to Fork” strategy